2003
DOI: 10.1128/jvi.77.15.8237-8248.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Depletion of Human Immunodeficiency Virus Type 1 and Simian Immunodeficiency Virus with β-Cyclodextrin Inactivates and Permeabilizes the Virions: Evidence for Virion-Associated Lipid Rafts

Abstract: Recent evidence suggests that human immunodeficiency virus type 1 (HIV-1) particles assemble and bud selectively through areas in the plasma membrane of cells that are highly enriched with glycosylphosphatidylinositol-anchored proteins and cholesterol, called lipid rafts. Since cholesterol is required to maintain lipid raft structure and function, we proposed that virion-associated cholesterol removal with the compound 2-hydroxy-propyl-␤-cyclodextrin (␤-CD) might be disruptive to HIV-1 and simian immunodeficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
205
3
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(224 citation statements)
references
References 63 publications
14
205
3
2
Order By: Relevance
“…In addition, the effect of Imiq on these parameters was abrogated by A151. Finally, we demonstrated that removal of viral RNA from HIV-1 particles with ␤-CD resulted in complete loss of the ability of these RNA-depleted HIV-1 particles to induce TRAIL expression by pDC (25). These results demonstrate that TLR7 is the only TLR that is required for HIV-induced transformation of pDC into IKpDC.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In addition, the effect of Imiq on these parameters was abrogated by A151. Finally, we demonstrated that removal of viral RNA from HIV-1 particles with ␤-CD resulted in complete loss of the ability of these RNA-depleted HIV-1 particles to induce TRAIL expression by pDC (25). These results demonstrate that TLR7 is the only TLR that is required for HIV-induced transformation of pDC into IKpDC.…”
Section: Discussionmentioning
confidence: 55%
“…We depleted ssRNA from HIV-1 particles by treatment with 80 mM ␤-cyclodextrin (HIV ␤CD ), a chemical modification that induces a hole in the virion capsid, liberating ssRNA but retaining capsid proteins as previously shown (25). These RNA-free particles were used for the culture of pDC (SI Fig.…”
Section: Generation Of Trail ؉ Pdc Hiv Occurs After Endosomal Acidifimentioning
confidence: 99%
“…Further, the viral glycoprotein distribution in the HSV virion envelope has been shown to be nonrandom, which has been hypothesized to be caused by association of viral glycoproteins with lipid rafts (17). In addition, we have found that, like for human immunodeficiency virus (15,27), cholesterol in the PRV envelope is required for infectivity, since depletion of cholesterol from PRV preparations by using 10 mM MCD completely abolished PRV's ability to successfully infect susceptible cells (data not shown). Therefore, it will be interesting to dissect the exact role of lipid rafts during alphaherpesvirus particle formation.…”
Section: Vol 78 2004 Lipid Raft Association Of Prv Glycoproteins 5285mentioning
confidence: 71%
“…Phosphatidylcholine accounts to 75% of total phospholipid [85] GP Viral envelopes are enriched in sphingomyelin [8,86] SP Envelope cholesterol is critical for structure and infectivity [87][88][89] ST 2 Phosphatidylserine stimulates entry of enveloped viruses [90,91] Mannose receptor binds to the ManLAM mannose caps of mycobacteria and mediates phagocytosis [92] GPI anchored proteins (host [35,36] and parasite [37] …”
Section: Glmentioning
confidence: 99%